2021
DOI: 10.3390/en14196305
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Based Green Workplace Practices as a Means of Conserving Energy and Other Natural Resources in the Manufacturing Sector

Abstract: The purpose of this research is to analyze the role of organizational culture in fostering green practices in the workplace while investigating the mediating role of intrinsic motivation in the context of energy conservation. Based on a cross-sectional quantitative study with a sample of 203 employees from the manufacturing sector, the hypothesized relationships were verified. Based on the mediation analysis, statistical analyses revealed positive relationships between organizational culture and green workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 136 publications
1
6
0
Order By: Relevance
“…In line with recent works (Bulińska‐Stangrecka & Bagieńska, 2021; Griese et al, 2021; Mohter & Fernando, 2020), we showed that single dimensions of corporate culture would either form success factors or barriers of emission reduction. Hence, this multi‐dimensional focus is necessary to understand to which degree corporate culture is defensive or open‐minded regarding emission reduction (Baumgartner, 2009, 2014).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with recent works (Bulińska‐Stangrecka & Bagieńska, 2021; Griese et al, 2021; Mohter & Fernando, 2020), we showed that single dimensions of corporate culture would either form success factors or barriers of emission reduction. Hence, this multi‐dimensional focus is necessary to understand to which degree corporate culture is defensive or open‐minded regarding emission reduction (Baumgartner, 2009, 2014).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
“…Previous works in the construction or manufacturing sector demonstrate the usefulness of layers and dimensions as a path toward the identification of cultural success factors and barriers (Bulińska‐Stangrecka & Bagieńska, 2021; Caldera et al, 2019; Wong & Zapantis, 2013). By measuring corporate culture along seven dimensions (sense of community, strategic orientation, leadership, team collaboration, communication, team structure, informal relationships), Bulińska‐Stangrecka and Bagieńska (2021) found a significant influence of corporate culture on the conservation of energy and other natural resources in the manufacturing sector.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant research gaps remain in examining sector-specific research [6] and applying mixed methods research to examine occupant energy behaviour, with most research to date focusing on observed occupant behaviour rather than why or how behaviour is generated [14]. The limited research conducted in manufacturing workplaces primarily focuses on manufacturing technologies and energy efficiency processes [15], rather than on employees or taking a whole system approach. To succeed in reducing business energy demand and achieving net zero, there is a need to understand the magnitude of factors that influence energy use in all work environments and fill these research gaps.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of OC for ensuring the sustainability of the enterprise was also emphasized [ 53 ]. OC is also important for strengthening green practices in the workplace [ 54 ]. OC is extremely dynamic and complex [ 55 ] and consequently receives attention in all areas [ 56 ], including, e.g., task performance [ 57 ].…”
Section: Introductionmentioning
confidence: 99%